Evaluating the Effectiveness of Online Educational Modules and Interactive Workshops in Alleviating Symptoms of Mild to Moderate Depression: A Pilot Trial. (November 2020) - Murillo, Luis A.; Follo, Emily; Smith, April; Balestrier, Julienne; Bevvino, Deborah L.
Introduction: Depression is a common health concern in primary care with barriers to treatment well documented in the literature. Innovative online psychoeducational approaches to address barriers to care have been well received and can be cost effective. This pilot trial evaluated the effectiveness of an online psychoeducation curriculum intended to alleviate symptoms of depression while utilizing minimal staff resources. Methods: A small (n = 29) randomized control pilot study was conducted. Online psychoeducational content was delivered in 5 to 10-minute videos over 8 weeks. Participants engaged in moderated discussions on workshop topics. The Patient Health Care Questionnaire (PHQ-9) was used to measure pre/post scores. Two Likert scale questions were used to determine subjective changes in understanding of depression and coping skills. Results: Paired T -test analysis showed an average PHQ-9 improvement of 4.37 ( P = .01) in the intervention arm and 1.81 ( P = .172) in the control group. No significant difference in delta PHQ-9 score was found between groups via difference in difference analysis ( P = .185). Effect size was 0.59. No improvement in Likert scores for question 1 or 2 were detected by paired T test in either group. Conclusion: This pilot trial of interactive online psychoeducational content shows initial promise as there was a significant improvement in PHQ-9 scores within the intervention arm. The comparison of delta scores between intervention and control arms was not statistically significant although this is likely due to the underpowered nature of the pilot trial. This data trend justifies the need for a larger validation trial of this intervention.